School Privatization and Socio-Economic Segregation: An International Comparison of Effects on Student Global Competence Using PISA 2018 - Molina, Andres; Gallo Cordoba, Beatriz (International Journal of Education Policy and Leadership, 2025)
School systems worldwide struggle with socio-economic segregation, often worsened by private schooling, which affects student learning and inequality. By dividing students along socioeconomic lines, both private schools and segregation can affect the development of essential skills for the twenty-first century. This study examines the link between private schooling, social segregation, and student global competence across 69 countries using PISA 2018 data. Multilevel models are used to estimate levels of social segregation and the association with private schooling and variations in student global competence between schools. While private school students tend to have higher global competence, countries with greater private enrolment exhibit lower average global competence, higher segregation, and wider global competence gaps between schools. Social segregation, driven by private schooling, is a key factor to explain global competence inequalities within countries.